2021
DOI: 10.3389/fimmu.2020.623199
|View full text |Cite
|
Sign up to set email alerts
|

A Decade Experience on Severe Combined Immunodeficiency Phenotype in Oman, Bridging to Newborn Screening

Abstract: IntroductionSevere combined immunodeficiency (SCID) results from various monogenic defects that impair immune function and brings on early severe and life-threatening infections. The main stay of treatment for SCID is hematopoietic stem cell transplant (HSCT) with near normal survival at 5 years for an early transplant done at or before the age of 3.5 months of life and the patient is maintained free of infections. Although overall rare, it constitutes a major burden on affected children, their families and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…The main encountered IEIs were phagocytic defects (35%), followed by PAD (20.7%) and CID (17.8%) ( 8 ). In contrast, a study from our center demonstrated a higher incidence of SCID among an Omani pediatric population (4/100,000) compared to the earlier published data ( 9 ). Such epidemiological discrepancies in Oman can suggest underreporting of IEI in such retrospective reports.…”
Section: Introductioncontrasting
confidence: 96%
“…The main encountered IEIs were phagocytic defects (35%), followed by PAD (20.7%) and CID (17.8%) ( 8 ). In contrast, a study from our center demonstrated a higher incidence of SCID among an Omani pediatric population (4/100,000) compared to the earlier published data ( 9 ). Such epidemiological discrepancies in Oman can suggest underreporting of IEI in such retrospective reports.…”
Section: Introductioncontrasting
confidence: 96%
“…It is worth mentioning that delayed diagnosis and misdiagnosis mainly reflect the poor knowledge about IEI among general practitioners/pediatricians. In this study, the median diagnostic delay was 1.5 (0.17-5.0) years, which was less than the previous cohort of 98 Iranian patients (6.1 years) in 2016 (4) and the Middle East and North Africa (MENA) Registry (3.4 years) ( 16); However, it was longer than the reported diagnostic delay (10 months) in the latest update on the Iranian National Registry of Primary Immunodeficiencies (10), as well as recent surveys in Pakistan ( 6) Oman (17), and Kuwait (18). In the present study, the diagnostic delay in HIES patients was longer than other PID patients.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, anticipating the possibility of NBS expansion has resulted in the generation of a study defining how SCID might be added to the program. Finally, NHS was introduced nationally in Oman after limited pilot testing in 2002 [ 1391 ]. Experiences with this program are detailed elsewhere along with the challenges of adding NBS to the public health system in a developing economy [ 1392 , 1393 ].…”
Section: Resultsmentioning
confidence: 99%